Characterisations of Partially Purified Peptides with Antimicrobial Activity from the Skin Secretion of Staurois guttatus (Family: Ranidae) in Sarawak, Malaysia - Muhammad Haziq Anwar, Azlan (Universiti Malaysia Sarawak (UNIMAS), 2017)
In frog skin secretions, there are antimicrobial peptides (AMP) which are important for their immune defence system and found out to be a potential antimicrobial agent. This study investigated and performed physical characterisation of partially purified AMP from Staurois guttatus based on electrophoresis method and also performed chemical characterisation of the partially purified AMP from Staurois guttatus. The skin secretion of S. guttatus was collected from several individuals of the species partially purified later using C18 Sep Pak cartridge. After that, Tricine SDS PAGE was performed on the partially purified skin secretion which displayed the presence of peptides with size of 6.6 kDa. The antimicrobial activity of the peptides was tested by disk diffusion test, broth microdilution test against S. aureus, E. coli and C. albicans. The disk diffusion test demonstrated clear inhibition zones of peptides against bacteria and fungus. Through microdilution test, S. guttatus peptide displayed lowest MIC value against S. aureus at concentration of 125 sg/mL, while against E. coli was 250 sg/mL. Differently, no MIC value was observed with peptides against C. albicans. Furthermore, in haemolytic assay peptides exhibited more than 50% haemolysis activity towards human erythrocytes. In conclusion, the presence of peptide bands lower than 10 kDa exhibit inhibition activity against bacteria and fungus on suitable concentration or volume, but not towards human erythrocytes but can be initiatively used in wound healing.